Potato Mosaic Leaf Curl Virus - Tangriyev Tursunpo'lat Chorshanbiyevich (Web of Journals Publishing, 2023)
This article provides information on potato mosaic leaf curl virus disease, its symptoms and control measures.
Keywords: protect plants, diseases and pests, climate change, viruses, disease symptoms, potato mosaic virus.